Development and testing of a decision aid for women considering delayed breast reconstruction. Issue 3 (March 2018) - Metcalfe, Kelly; Zhong, Toni; O'Neill, Anne C.; McCready, David; Chan, Linda; Butler, Kate; Brennenstuhl, Sarah; Hofer, Stefan O.P.
Summary: Background: The decision to have post-mastectomy breast reconstruction (PMBR) is highly complex and many women feel ill equipped to make this decision. Decision aids have been advocated to promote patient involvement in decision-making by streamlining and standardizing communication between the patient and the health care professional. In this study, we report on the development and testing of a decision aid (DA) for breast cancer survivors considering delayed PMBR. Methods: The DA was developed and evaluated in three phases. The first phase included the development of the DA with input and review by practitioners and key stakeholders. The second phase involved pilot testing of the feasibility and acceptability of the DA with a convenience sample of women with delayed PMBR. The third phase involved a pretest/post-test evaluation of the DA for women who were making decisions about their PMBR options. Results: The DA was developed using the Ottawa Decision Support Framework. In the second phase of the study, 21 women completed the acceptability survey, of whom 100% reported that they would recommend the DA to other women. In the third phase, decisional conflict decreased significantly (p < 0.001) and knowledge increased significantly (p < 0.001) from prior to using the DA to 1–2 weeks after using the DA. Conclusions: The DA is feasible and acceptable to women considering delayed PMBR. Furthermore, the DA is effective at reducing decisional conflict and increasing knowledge about delayed PMBR. The DA is an appropriate tool to be used in addition with standard care in women considering PMBR.